2011
DOI: 10.1063/1.3626045
|View full text |Cite
|
Sign up to set email alerts
|

Antimony desinsertion reaction from SbxCoSb3−x

Abstract: Modeling the hydration of mono-atomic anions from the gas phase to the bulk phase: The case of the halide ions F−, Cl−, and Br− J. Chem. Phys. 136, 044509 (2012) Structure, energetics, and reactions of alkali tetramers J. Chem. Phys. 136, 014306 (2012) Influence of solute-solvent coordination on the orientational relaxation of ion assemblies in polar solvents J. Chem. Phys. 136, 014501 (2012) Theoretical study of the aqueous solvation of HgCl2: Monte Carlo simulations using second-order Moller-Plessetder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The observed lattice‐parameter expansion and CoSb 2 formation are due to antimony self‐insertion, as previously reported4951 and the subsequent collapse of the CoSb 3 phase under Giga‐Pascal pressures. As above, the effect is more pronounced in the RT‐processed sample as compared to the HT‐processed sample as (1) the strain energy (attendant with dislocations) is higher in the RT sample; and (2) Sb de‐insertion occurs at temperatures greater than 180 °C (at ambient pressure) as reported by Miotto et al50 Hence Sb de‐insertion, nucleation, and growth occur upon cooling the HT sample from 400 °C to room temperature. This effect is supported by SEM (Figure 3).…”
Section: Resultssupporting
confidence: 52%
“…The observed lattice‐parameter expansion and CoSb 2 formation are due to antimony self‐insertion, as previously reported4951 and the subsequent collapse of the CoSb 3 phase under Giga‐Pascal pressures. As above, the effect is more pronounced in the RT‐processed sample as compared to the HT‐processed sample as (1) the strain energy (attendant with dislocations) is higher in the RT sample; and (2) Sb de‐insertion occurs at temperatures greater than 180 °C (at ambient pressure) as reported by Miotto et al50 Hence Sb de‐insertion, nucleation, and growth occur upon cooling the HT sample from 400 °C to room temperature. This effect is supported by SEM (Figure 3).…”
Section: Resultssupporting
confidence: 52%
“…Also, the effect of pressure on the guest mode of LaFe 4 Sb 12 was recently calculated by Martinotto et al Moreover, a recent theoretical work has reported an improvement of the thermoelectric properties of CoSb 3 under high pressure . Several studies have discussed the effect of pressure on the crystal structure of CoSb 3 and reported the equation of states and the bulk modulus of CoSb 3 and other skutterudites. They also reported an antimony insertion reaction under high external pressure in the antimonide and arsenide unfilled skutterudites above 20 GPa at room temperature and at pressures lower than 10 GPa under high pressure–high temperature (HP–HT) conditions. , Until now, only thermoelectric and transport properties of these Sb x Co 4 Sb 12– x samples were studied . Other properties such as lattice dynamics under high pressure of CoSb 3 are missing.…”
Section: Introductionmentioning
confidence: 92%
“…57 Several studies have discussed the effect of pressure on the crystal structure of CoSb3 and reported the equation of states and the bulk modulus of CoSb3 and other skutterudites. [58][59][60][61][62][63][64][65] They also reported an antimony insertion reaction under high external pressure in the antimonide and arsenide unfilled skutterudites above 20 GPa at room temperature [60][61][62][63][64][65] and at pressures lower than 10 GPa under high pressure-high temperature (HP-HT) conditions. 64,65 Until now, only thermoelectric and transport properties of these SbxCo4Sb12-x samples were studied.…”
Section: Raman Experiments Under Pressure Have Been Recently Performementioning
confidence: 99%
See 1 more Smart Citation